Obstructive reinke edema - Ruggeri, Carlos S.; Latourrette, Dora Cristina; García Pita, Elián; Martínez Font, Agustín; Fernández , Florencia; Vega, Andrés (Revista del Hospital Italiano de Buenos Aires, 2017)
Introduction: the Reinke edema is an accumulation of fluid in the outer layer of the lamina propria of the vocal cords. Causes dysphonia and rarely produces respiratory obstruction. Objectives: to determine the rate of resolution of the severe inspiratory dyspnea caused by bilateral Reinke edema of vocal cords with surgical treatment. Design: descriptive and retrospective study. Material and methods: review of the electronic medical records of all patients who consulted and were treated for severe inspiratory dyspnea caused by bilateral Reinke edema of the vocal chords in the Hospital Italiano de Buenos Aires between February 2007 and April 2015. Results: four women were treated, consulted for severe inspiratory dyspnea. Smoked more than 30 cigarettes per day. The surgical technique consisted in to resect all the bilateral polypoid edema, while preserving the free edge of the vocal cords. Conclusions: the obstructive Reinke edema is an infrequent pathology. The rate of resolution of the severe inspiratory dyspnea in the four patients treated was 100%. The total resection of the edema and mucosa excess, preserving a small sector to cover the free edge of the vocal cord (cordectomy vs cordotomy) was the preferred surgical technique